2023
DOI: 10.1007/s00392-023-02272-7
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography-guided versus angiography-guided percutaneous coronary intervention in acute coronary syndrome: a meta-analysis

S. Macherey-Meyer,
M. M. Meertens,
S. Heyne
et al.

Abstract: Background Percutaneous coronary intervention (PCI) is standard of care in patients with acute coronary syndrome (ACS) suitable for interventional revascularization. Intracoronary imaging by optical coherence tomography (OCT) expanded treatment approaches adding diagnostic information and contributing to stent optimization. Objectives This meta-analysis aimed to assess the effects of OCT-guided vs. angiography-guided PCI in treatment of ACS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…These risks might overshadow the clinical benefits of OCT. However, the meta-analysis of observational studies indicated a significant reduction in MACE and TLR with OCT-guided PCI, aligning with previous research ( 67 , 70 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These risks might overshadow the clinical benefits of OCT. However, the meta-analysis of observational studies indicated a significant reduction in MACE and TLR with OCT-guided PCI, aligning with previous research ( 67 , 70 ).…”
Section: Discussionsupporting
confidence: 88%
“…Given the potential introduction of confounding factors in observational studies ( 71 ), we conducted separate meta-analyses of evidence from RCTs and observational studies for OCT-guided PCI. This approach differs from previous meta-analyses, showing OCT's significant advantages are more pronounced in observational studies ( 67 , 70 ), consistent with previous high-quality RCTs ( 29 , 49 , 53 ).…”
Section: Discussionsupporting
confidence: 74%